Narcolepsy treatment: pharmacological and behavioral strategies in adults and children - Franceschini, Christian; Pizza, Fabio; Antelmi, Elena; Folli, Maria Claudia; Plazzi, Giuseppe (Sleep & breathing, 2020)
Narcolepsy is a disabling, rare, and chronic sleep disorder, currently classified as distinct central nervous system hypersomnia in narcolepsy type 1 (NT1) and narcolepsy type 2 (NT2). Although today a reliable pathogenic hypothesis identifies the cause of NT1 as an autoimmune process destroying hypocretin-producing cells, there is no cure for narcolepsy, and the symptomatic pharmacological available treatments are not entirely effective for all symptoms. Behavioral therapies play a synergistic role in the disease treatment. We here review the available therapeutic options for narcolepsy, including symptomatic pharmacological treatments as well as behavioral and psychosocial interventions that could help clinicians improve the quality of life of patients with narcolepsy in adulthood and childhood.